Marine accidents ascribe to man or machine? - Ramprasad, BK (The International Hydrographic Review, 2025)
The International shipping industry is responsible for the carriage of around 90 % of the world trade (ICS, 2024). The efficient Marine Safety Information Services (MSIS) have been made available to the mariner besides national / international regulations using the upgraded navigational tools like ENCs and virtual e-navigation. A roadmap to switch over to the S-100 data model and generating new S-101 ENCs has already been prepared by the IHO. Irrespective of technological developments, marine accidents are increasing worldwide every year and the reports (MAIB, 2017) reveals that lack of trained manpower on bridge, lack of familiarization to the digital equipment and its use was the root cause of many of these marine casualties. The sub working group members of the NCWG have prepared a document on the Future of the Paper Nautical Chart (FOTPNC) in view of maximal use of ECDIS and ENCs onboard ships. The present study after analysing the aforesaid investigation reports reveals that the increase of marine accidents may be attributed to both man and machine.